2014
DOI: 10.3389/fict.2014.00001
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Dissipative Channels for Realizing Schrödinger Cats in SQUIDs

Abstract: We show that by engineering the interaction with the environment, there exists a large class of systems that can evolve irreversibly to a cat state. To be precise, we show that it is possible to engineer an irreversible process so that the steady state is close to a pure Schrödinger's cat state by using double well systems and an environment comprising two-photon (or phonon) absorbers. We also show that it should be possible to prolong the lifetime of a Schrödinger's cat state exposed to the destructive effect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 84 publications
0
22
0
Order By: Relevance
“…In this work, we present hybrid setups that are able to achieve a two-phonon coherent coupling between a mechanical mode and a spin qubit, described as a two-level system (TLS). It is known for systems involving some kind of twoparticle interaction plus a nonlinearity [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], that the mechanical system can evolve into motional cat states. Although these states are ultimately washed out by decoherence, our proposed setup features non-classical transient states, characterized by a negative Wigner function, during timescales that can extend up to seconds.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we present hybrid setups that are able to achieve a two-phonon coherent coupling between a mechanical mode and a spin qubit, described as a two-level system (TLS). It is known for systems involving some kind of twoparticle interaction plus a nonlinearity [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36], that the mechanical system can evolve into motional cat states. Although these states are ultimately washed out by decoherence, our proposed setup features non-classical transient states, characterized by a negative Wigner function, during timescales that can extend up to seconds.…”
mentioning
confidence: 99%
“…Transient non-classical states.-The high quality factors of state-of-the-art nanoresonators [65] allows for nonclassical states to develop and evolve in timescales of tenth of a second before every trace of coherence is washed out. We show this by plotting the evolution of the "cattiness" C = N (ρ)/N (ρ cat ), defined by dividing the integrated negative parts of the Wigner function of the state by that of a reference cat state [32], so that C > 0 only for nonclassical states and = 1 for cat states. The results shown in Fig.…”
mentioning
confidence: 99%
“…Systems with such symmetries are thus strong candidates for studying NLD in the quantum regime. Moreover, it was suggested that engineering of NLD might be feasible [29][30][31]. Exploiting the reduced disentanglement in systems with NLD is a promising path towards realizing entanglement based technologies.…”
Section: Discussionmentioning
confidence: 99%
“…Among these are carbon-based nanomechanical systems like graphene and carbon nanotubes [25,27,28]. Additionally, there have been reports of inducing nonlinear dissipation in optome- * Electronic address: andreas.isacsson@chalmers.se chanical systems [29,30], and suggestions for possible emergence of NLD in solid state quantum devices [31].…”
Section: Introductionmentioning
confidence: 99%
“…Sufficiently large SCSs for applications in quantum information ( 2 a » ) [18,19] and generalized Fock states [20] have recently been generated in microwave cavities with the assistance of superconducting qubits. Moreover, enhanced stabilization of SCSs in a cavity has recently been reported using a specially designed lossy environment [18,21], with the aim of producing robust quantum memory [22]. This loss engineering could also provide a complementary (continuous) method of SCS amplification in circuit QED.…”
Section: Introductionmentioning
confidence: 99%